2022
DOI: 10.3389/fimmu.2022.823157
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response at the Tumor-Immune Interface

Abstract: The tumor-immune interface has surged to primary relevance in an effort to understand the hurdles facing immune surveillance and cancer immunotherapy. Reports over the past decades have indicated a role for the unfolded protein response (UPR) in modulating not only tumor cell fitness and drug resistance, but also local immunity, with emphasis on the phenotype and altered function of immune cells such as myeloid cells and T cells. Emerging evidence also suggests that aneuploidy correlates with local immune dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 183 publications
(224 reference statements)
0
11
0
Order By: Relevance
“…Given the enormous enrichment of the UPR in NSD3 -amplified tumors ( Figure 1 E) and the tight junction between UPR signaling and anti-tumor immunity [ 35 , 36 ], we sought to determine whether the UPR is associated with the suppressive immunological features of NSD3 -amplified LUSC. Apart from displaying an upregulated expression pattern ( Figure 6 A), the high UPR gene signature predicted a poor prognosis, particularly in the NSD3 -amplified group ( Figure 6 B, Supplementary Figure S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the enormous enrichment of the UPR in NSD3 -amplified tumors ( Figure 1 E) and the tight junction between UPR signaling and anti-tumor immunity [ 35 , 36 ], we sought to determine whether the UPR is associated with the suppressive immunological features of NSD3 -amplified LUSC. Apart from displaying an upregulated expression pattern ( Figure 6 A), the high UPR gene signature predicted a poor prognosis, particularly in the NSD3 -amplified group ( Figure 6 B, Supplementary Figure S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, GSEA analysis also confirmed significant enrichment of some immune-related pathways in cluster 1, including coagulation, inflammatory response, and IL6/JAK/STAT3 signaling. The UPR is proven to not only affect the growth and survival of tumor cells but also play an essential role in remodeling the TIME ( Zanetti et al, 2022 ). Batista et al identified that the UPR participates in the macrophage polarization in the TIME by activating the IRE1α/XBP1 axis, resulting in upregulation of IL-6, IL-23, arginase 1, CD86, and PD-L1 that lead to local immune dysregulation ( Batista et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activation of the UPR was found in a wide range of tumors, including bladder cancer, cutaneous melanoma, and liver cancer ( Houessinon et al, 2016 ; Wan et al, 2020 ; Zhu et al, 2021 ). Apart from a direct impact on tumor biology, the UPR also has the ability to remodel the tumor immune microenvironment (TIME) to regulate the crosstalk between immune cells, which serves an essential function in immune surveillance and immune escape ( Zanetti et al, 2022 ). Mahadevan et al demonstrated that the UPR can modulate the phenotype of dendritic cells and CD8 + T cells to facilitate tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…The exquisite persistence of memory T cells in solid tumors is indicative of an intrinsic resistance to the metabolic stress presented by the TME. Perturbations to metabolic homeostasis such as amino acid deprivation, glucose starvation, and hypoxia promote the induction of the unfolded protein response (UPR) ( Pan et al, 2003 ; Bi et al, 2005 ; Qiu et al, 2010 ; Bobak et al, 2016 ; Zanetti et al, 2022 ) in the endoplasmic reticulum (ER) of cells. As the hub of protein translation, the ER is equipped with three stress sensors, protein kinase RNA-like endoplasmic reticulum kinase (PERK), inositol-requiring enzyme 1 (IRE1α), and activating transcription factor 6 (ATF6) poised to sense a burden of unfolded/misfolded proteins in the ER lumen (ER stress) or other challenges to ER function such as lipid dysregulation ( Hetz, 2012 ).…”
Section: Primer: Immunotherapy and T Cell Biologymentioning
confidence: 99%